The Design of a Hall Effect Current Transformer and Examination of The Linearity with Real Time Parameter Estimation - (:unkn) unknown (KAUNAS UNIV TECHNOLOGY, 2010)
G. Gokmen, K. Tuncalp. The Design of a Hall Effect Current Transformer and Examination of The Linearity with Real Time Parameter Estimation // Electronics and Electrical Engineering. - Kaunas: Technologija, 2010.-No. 5(101). - P. 3-8. Today, the Hall sensor based current measurement is being widely used as they have both AC and DC current measurement capability. The factors such as ratiometric error or Hall sensor, earth or other magnetic effects in sensor location, sensitivity errors originating from temperature or magnetic core, deteriorates measurement linearity. This requires that measurement results are evaluated with mathematical analysis methods. In this study, a closed loop Hall Effect current transformer was designed and its linearity in measurement results is examined by real time parameter estimation based on the least squares method so measurement accuracy was improved and real time observation of linearity error was provided III 12, bibl 24, tabl 1 (in English, abstracts in English, Russian and Lithuanian).